Obinutuzumab plus bendamustine versus bendamustine monotherapy in patients with rituximab-refractory indolent non-Hodgkin lymphoma (GADOLIN): a randomised, controlled, open-label, multicentre, phase 3 trial - Sehn, Laurie H; Chua, Neil; Mayer, Jiri; Dueck, Gregg; Trněný, Marek; Bouabdallah, Kamal; Fowler, Nathan; Delwail, Vincent; Press, Oliver; Salles, Gilles; Gribben, John; Lennard, Anne; et al. (The Lancet. Oncology, 2016)
BACKGROUND: Patients with indolent non-Hodgkin lymphoma who fail to achieve adequate disease control with rituximab-based treatment have few treatment options and a poor prognosis. We aimed to assess a combination of obinutuzumab (GA101), a novel glyco-engineered type II anti-CD20 monoclonal antibody, and bendamustine in this patient population. METHODS: In this open-label, randomised, phase 3 study (GADOLIN), patients aged 18 years or older with histologically documented, CD20-positive indolent non-Hodgkin lymphoma refractory to rituximab were enrolled at 83 hospital and community sites in 14 countries in Europe, Asia, and North and Central America. Patients were randomly assigned (1:1) using a hierarchical dynamic randomisation scheme stratified by indolent non-Hodgkin lymphoma subtype, rituximab-refractory type, number of previous therapies, and geographical region, to receive induction treatment (six 28-day cycles) with obinutuzumab plus bendamustine or bendamustine monotherapy, both given intravenously. Obinutuzumab plus bendamustine dosing was obinutuzumab 1000 mg (days 1, 8, and 15, cycle 1; day 1, cycles 2-6) plus bendamustine 90 mg/m(2) per day (days 1 and 2, cycles 1-6), and bendamustine monotherapy dosing was 120 mg/m(2) per day (days 1 and 2, all cycles). Non-progressing patients in the obinutuzumab plus bendamustine group received obinutuzumab maintenance (1000 mg every 2 months) for up to 2 years. The primary endpoint was progression-free survival in all randomised patients, as assessed by an independent review committee. Safety was assessed in all patients who received any amount of obinutuzumab or bendamustine. This study is registered with ClinicalTrials.gov, number NCT01059630, and has stopped recruiting patients. FINDINGS: Between April 15, 2010, and Sept 1, 2014, when the study was stopped after a pre-planned interim analysis, 396 patients were randomly assigned (194 to obinutuzumab plus bendamustine and 202 to bendamustine monotherapy). After a median follow-up time of 21·9 months (IQR 12·1-31·0) in the obinutuzumab plus bendamustine group and 20·3 months (9·5-29·7) in the bendamustine monotherapy group, progression-free survival was significantly longer with obinutuzumab plus bendamustine (median not reached [95% CI 22·5 months-not estimable]) than with bendamustine monotherapy (14·9 months [12·8-16·6]; hazard ratio 0·55 [95% CI 0·40-0·74]; p=0·0001). Grade 3-5 adverse events occurred in 132 (68%) of 194 patients in the obinutuzumab plus bendamustine group and in 123 (62%) of 198 patients in the bendamustine monotherapy group. The most frequent grade 3 or worse adverse events were neutropenia (64 [33%] in the obinutuzumab plus bendamustine group vs 52 [26%] in the bendamustine monotherapy group), thrombocytopenia (21 [11%] vs 32 [16%]), anaemia (15 [8%] vs 20 [10%]) and infusion-related reactions (21 [11%] vs 11 [6%]). Serious adverse events occurred in 74 patients (38%) in the obinutuzumab plus bendamustine group and in 65 patients (33%) in the bendamustine monotherapy group, and deaths due to adverse events occurred in 12 patients (6%) and 12 patients (6%), respectively. Three (25%) of 12 adverse event-related deaths in the obinutuzumab plus bendamustine group and five (42%) of 12 in the bendamustine monotherapy group were treatment related. INTERPRETATION: Obinutuzumab plus bendamustine followed by obinutuzumab maintenance has improved efficacy over bendamustine monotherapy in rituximab-refractory patients with indolent non-Hodgkin lymphoma, with manageable toxicity, and is a new treatment option for patients who have relapsed after or are no longer responding to rituximab-based therapy. FUNDING: F Hoffmann-La Roche Ltd.
Keywords: Bendamustine Hydrochloride; Rituximab; Male; Survival Rate; lokální recidiva nádoru; Antineoplastic Combined Chemotherapy Protocols; následné studie; nehodgkinský lymfom; prognóza; Neoplasm Staging; chemorezistence; Aged; mužské pohlaví; senioři; Lymphoma, Non-Hodgkin; rituximab; Follow-Up Studies; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Neoplasm Recurrence, Local; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Prognosis; bendamustin hydrochlorid; Drug Resistance, Neoplasm; Female; lidé středního věku; staging nádorů; míra přežití; Middle Aged